Austenite Grain Growth Kinetics in API X65 and X70 Line-Pipe Steels during Isothermal Heating - Asiful Hossain Seikh; Mahmoud S. Soliman; Abdulhakim AlMajid; Khaled Alhajeri; Waleed Alshalfan (Advances in Materials Science and Engineering)
The aim of the present work is to investigate the microstructural behavior of austenite grain size (AGS) during the reheating process of two different API steel grades (X65 and X70). The steel samples were austenitized at 1150°C, 1200°C, and 1250°C for various holding times from 10 to 60 minutes and quenched in ice water. The samples were then annealed at 500°C for 24 hours to reveal the prior AGS using optical microscopy. It was noticed that the AGS in X65 grade is coarser than that of X70 grade. Additionally, the grain size increases with increasing the reheating temperature and time for both steels. The kinetics of grain growth was studied using the equation dn-d0n=Atexp-Q/RT , where d is the measured grain size, do is the initial grain size, n is the grain size exponent, t is the heating time, T is the heating temperature, Q is the activation energy, R is the gas constant, and A is a constant. To characterize the grain growth process the values of n, Q, and A were determined. Good agreement is obtained between the prediction of the model and the experimental grain size values.